Pathway to Accessing Social Care Service Among Older Adults: A Perspective of Demand Spillover Theory. - Li, Xuena; Zhang, Hengyuan; Wan, Jiahui; Chauhan, Anjali (Health & Social Care in the Community, 2025)
There is a serious mismatch in China's social care system for older adults. To address the issue of imprecise service targeting, this study employs the demand spillover theory and survey data from three cities and six counties in China. Results from logistic regression analysis identify a hierarchical structure of influencing factors. The analysis shows that family care resources, particularly marital status and living arrangements, exert the strongest effect on care choices. Meanwhile, socioeconomic resources such as urban residence and higher income serve as key enablers for accessing formal care. These findings reveal a resource‐based screening mechanism that channels older adults with different needs into distinct care pathways, ultimately explaining the paradox of insufficient effective demand amid a rapidly aging population.